(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2003)
Fusulinaceans consisting of 56 species belonging to 30 genera are distinguished from the Surmaq Formation distributed in the Abadeh region, central Iran. Among them, 23 species, including three species newly proposed: Parafusulina tarazi, Skinnerella abadehensis, and Sphaerulina iranensis, are systematically described and discussed. Many microphotographs of fusulinaceans are illustrated so as to understand their wide intraspecific variation and to compare them with other faunas from the Tethyan regions. The Surmaq Formation is biostratigraphically divided into six zones from lower to upper: Darvasites ordinatus, Pseudofusulina quasifusuliniformis, Eopolydiexodina persica, Afghanella schencki, Neoschwagerina occidentalis, and Chusenella abichi. The first zone is probably Yakhtashian, the second is possibly Kubergandian, the third to fifth are Murgabian, and the last is Midian in age, based on the stratigraphic distribution and faunal correlation of neoschwagerinids and schwagerinids in Middle Permian formations of the Tethyan regions. Schwagerinids are dominant in these six zones, whereas almost all neoschwagerinids and verbeekinids are restricted to the fourth and fifth zones. Middle Permian fusulinacean faunas in South West Asian and Mediterranean Sea regions are well represented by those of the Surmaq Formation, and paleobiogeographically assignable to Province A (Western Tethyan Province). Fusulinacean faunas of Province A are largely different from those in Province B (Eastern Tethyan Province) by the very rare occurrence of typical Colania and Lepidolina, and from Province C (Panthalassan Province) by the presence of Afghanella and Sumatrina.